The Implementation of Imam Zarkasyi's Education Concept in Pesantren - Agung Ilham Prastowo; Tri Mulyanto (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aims to reveal the innovation of modern pesantren education carried out by the Ta'mirul Islam Islamic boarding school based on the perspective of Imam Zarkasyi. The challenges of contemporary progress demand that Islamic boarding schools need to improve their education system, both in terms of institutions, curriculum and philosophy and goals. K.H Imam Zarkasyi is an educational figure who succeeded in laying the foundation of the pesantren education system, thus inspiring the Ta'mirul Islam Islamic boarding school to adopt its education system. The method used in this research is descriptive qualitative, in which data collection is carried out in several ways, namely observation, interviews, and documentation. The results of this study indicate that the implementation of the Imam Zarkasyi education concept in the Ta'mirul Islam Islamic boarding school is carried out by integrating the Islamic education system and madrasah, integrating religious and general science, and cultivating the values of a life philosophy. In addition, the education system in Ta'mirul Islam can be used as a model for educational development in other pesantren.